THREE ARM UNSIGNALIZED INTERSECTION ON JALAN PERJUANGAN – JALAN KALIABANG BABELAN, NORTH BEKASI - Ardhan Rizakdy Fauzan; Harwidyo Eko Prasetyo; Andika Setiawan; Irnanda Satya Soeratmodjo (International Journal of Civil Engineering and Infrastructure, 2021)
The intersection of Jalan Perjuangan - Jalan Kaliabang Babelan, North Bekasi is experiencing high traffic flow. It is because the intersection area is a shopping area and a residential area so that traffic jams often occur during busy traffic jams. This research aims to see the degree of saturation and delay at the research location. This research was conducted using a method based on MKJI 1997. The results of the analysis in the morning, the maximum flow that occurs on weekdays is 5533.7 pcu / hour, the minimum flow on holidays is 3982.2 pcu / hour with the degree of saturation on working day in the morning is equal to 1.18, and the degree of saturation in morning on holidays is 1.30 with a delay in morning in holidays is 36.1 sec / pcu, the delay in morning on working day is 5.7 sec / pcu. The results of the analysis during the day that the maximum flow occurs on holidays is 3905.6 pcu / hour, the minimum flow on working day is 3551.9 pcu / hour with the degree of saturation on holiday is 1.11, the degree of saturation on weekdays in the afternoon is 0.83 with a delay on holiday is 26.97 sec / pcu, a delay on working day is 13.48 sec / pcu. The results of the analysis in the afternoon the maximum flow occurs on weekdays of 6304.8 pcu / hour, the minimum flow on holidays is 5869.1 pcu / hour with the degree of saturation on working day is 1.84, the degree of saturation on holidays is 1.55 with a delay on working day is 0.74 sec / pcu, and delay on holidays is 1.08 sec / pcu